An Assessment Approach to Urban Economic Resilience of the Rust Belt in China. (10th September 2021) - Man, Shan; Wu, Xiangli; Yang, Yongchun; Meng, Qingmin
Abstract : Urban economic resilience provides a novel perspective on the sustainable development of urban and regional economy. Selecting 37 prefecture-level cities in the Northeast China that also known as the rust belt in China as a regional study sample that has experienced significant economic decline and out-migration in the last 20 years compared to many other regions in China, this study aims to construct an index system using the data collected in 2005, 2010, and 2016. This study evaluates urban economic resilience including five socioeconomic aspects: diversity, capabilities related to revenue and expenditure, innovation environment, trend of development, and openness. We analyze the spatial and temporal evolution characteristics of urban economic resilience, explore the key factors contributing to urban resilience and then provide decision-making suggestions to enhance it. We find the following: (1) urban economic resilience in the Northeast China has gradually increased over time, but spatial heterogeneity of resilience was prominent. Specifically, coastal cities were more economically resilient than inland cities. (2) Urban economic resilience in the Northeast China is significantly contributed by the diversity of an economic system and the trend of development, which contribute to resilience with weights of 0.214 and 0.216, respectively. The dominant factors contributing to urban economic resilience are different among diverse urban economic types and size. (3) To enhance urban economic resilience, comprehensive economic cities need to focus on increasing the diversity of economic structures. Resource-based and old industrial cities should focus on raising the innovation environment. Coastal cities should focus on increasing the diversity of their economic structures and creating positive trends of economic and social development. Agricultural cities should focus on creating positive trends of economic and social development.